2010
DOI: 10.1673/031.010.14001
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Fitness Characters of Two Host Plant-Based Congeneric Species of the Banana Aphid,Pentalonia NigronervosaandP. Caladii

Abstract: Aphids and other phytophagous insects often show intra-specific variations in relation to host plant utilization. In several instances, intra-species variations lead to host-plant specialization. These are considered to be important source of speciation. In a recent study (Foottit RG et al. 2010. Zootaxa 2358: 25–38) two forms of the banana aphid, Pentalonia nigronervosa f typica Coquerel (Hemiptera: Aphididae) from banana hosts and P. nigronervosa f. caladii van der Goot collected from Zingiberaceae and Arace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In both study areas, susceptibility to the disease varied according to the genotype used, which is in agreement with reports from India and the Philippines (Thomas & Caruana, 2000; Geering, 2009). Moreover, Bhadra & Agarwala (2010) reported that under field conditions, the population of aphid vectors grows in response to the phenology of their respective host plants. Banana pseudostem colour influences aphid preference (Robson et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both study areas, susceptibility to the disease varied according to the genotype used, which is in agreement with reports from India and the Philippines (Thomas & Caruana, 2000; Geering, 2009). Moreover, Bhadra & Agarwala (2010) reported that under field conditions, the population of aphid vectors grows in response to the phenology of their respective host plants. Banana pseudostem colour influences aphid preference (Robson et al.…”
Section: Discussionmentioning
confidence: 99%
“…The aphid was initially reported to have occurred on member species of the Zingiberaceae and Araceae families, but morphological and morphometric studies confirmed that these aphids were in fact a separate species ( P. caladii ; Bhadra & Agarwala, 2010; Foottit et al. , 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The two earlier considered genotypes or forms can thus be easily considered as two species P. nigronervosa and P. caladii on the basis of their morphological, b iological and electrophoretic variat ions. Between the two species of Pentalonia tested in this study, the typica species exp ressed lower fitness on banana host plant than the caladii species fro m taro host plant [18]. Such a difference in response to host plants is suggestive of strong genotype (aphids)-environment (host plants) interactions indicating increased genetic variat ion.…”
Section: Discussionmentioning
confidence: 68%
“…In a recent study based on morphological and molecu lar d ifferences, the two forms of the banana aphid were given their species status, respectively, [17]. Bhadra and Agarwala [18] further recorded ecological and bio logical differences between P. caladii and P. nigronervosa from Araceae and Musaceae plants, respectively and considered these as full species.…”
Section: Introductionmentioning
confidence: 99%
“…Molting of third and fourth instars was monitored, and molted skin was removed soon after the measurements were recorded. The time interval in hours from the final molt to the production of the first nymph by an apterous adult aphid was recorded as the D 1st PG (Bhadra and Agarwala 2010). …”
Section: Methodsmentioning
confidence: 99%